Utilization of a Joint Point Regression Model for Predicting Mortality Rates of Common Cancers in Babol City - Pouyan Ebrahimi; Sara Khaleghi; Mohebat Vali; Sahar Delavari; Soraya Khafri; Mohsen Karami; Layla Shojaie; Hossein‐Ali Nikbakht (Cancer Reports)
ABSTRACT Background Cancer is a major cause of mortality. Timely information about cancer mortality trends is essential for prioritizing health programs. Aims This study aims to use a Joint point regression model to predict the mortality rates of the top 10 common cancers in Babol City. Methods This cross‐sectional study considered all registered cancer‐related deaths from 2013 to 2021 in the Babol University of Medical Sciences' death registration and classification system. Crude and age‐standardized rates and cancer trends were calculated and predicted for the next 5 years, overall and by type of cancer and gender. Results Over these 9years, 2417 deaths from the 10 common cancers were recorded. We observed an increase in mortality rates with a slope of 12.05% from 2013 to 2016, and a gentler slope of 3.2% from 2016 to 2021. Cancer mortality rates are predicted to increase by 6.43% in the next 5 years without intervention. Detailed analysis indicates that breast cancer will have the highest mortality rate during 2022–2026, rising by 13.6% annually. Predictions based on gender indicate that, breast cancer mortality will increase by 13.6% annually for women. Also, stomach cancer mortality rates will increase by 0.15% in men annually. Conclusion Cancer mortality in Babol remains a significant public health issue with an increasing trend. Nevertheless, these rising mortality rates require urgent interventions, including cancer prevention programs, increased access to medical services, and improved quality of life.